Livestock Depredation and Pastoralist Attitudes towards Carnivore in the Landscape of Lions Associated with Gambella National Park, Abobo District, Western Ethiopia - Getahun Gedif Abie; Krishnagouda Shankargouda Goudar; Hussein Ibrahim; Gezahegn Getachew (International Journal of Zoology)
The livelihoods of individuals in Ethiopia are severely affected by the livestock depredation from wild animals. The main objective of this study is to assess the incidences of livestock predation and pastoralist attitudes towards carnivore in the landscape of lions associated with Gambella National Park in the Abobo district of Western Ethiopia. The study was conducted between September 2017 and May 2018, utilizing a pretested semistructured questionnaire. Data analysis involved the utilization of multiple response analysis, Chi square test, Cramer’s V and Cohen’s Omega, Potential for Conflict Index2, and multinomial regression analysis. Anubis baboon (29.1%), leopard (20.5%), hyena (19.3%), lions (18.6%), and common fox (12.4%) were responsible for depriving cattle, sheep/goat, and fowls. The chi-square test, along with Cramer’s V and Cohen’s Omega, indicated a relatively smaller effect size for the anubis baboon (ω = 0.220) and the common fox (ω = 0.164), implying a consistent trend of livestock depredation across villages. In contrast, medium effect size for leopards (ω = 0.466), hyenas (ω = 0.449), and lions (ω = 0.324) indicated that livestock depredation across villages was moderately inconsistent. In terms of preventive measures, barns and active guarding were reported options to protect their livestock, with a small effect size (ω = 0.257). Moreover, increased trend of livestock predation was perceived by informants with small effect size (ω = 0.227). Many respondents expressed a negative attitude (73.51%) towards wild animals than positive (8.60%) and neutral (17.90%) attitudes with a small effect size (ω = 0.181). The Potential for Conflict Index2 revealed a low consensus for acceptance of livestock depredation by different predators and skewed responses indicating the predominance of negative attitudes, regardless of livestock losses to predators. The regression model revealed that sociodemographic elements such as age, education, and occupation influence people’s attitude. Hence, sustainable and culturally acceptable conservation measures are required to mitigate human-wildlife​ conflict.